Knowee
Questions
Features
Study Tools

(~P^(~Q^~R)) v (Q^R) v (P^R) <=> Rprove it without using truth table3 / 3

Question

Prove the equivalence:

( P( Q R))(QR)(PR)R(~P \land (~Q \land ~R)) \lor (Q \land R) \lor (P \land R) \Longleftrightarrow R

Prove it without using a truth table.

🧐 Not the exact question you are looking for?Go ask a question

Solution

To prove the equivalence (¬P(¬Q¬R))(QR)(PR)R(\neg P \land (\neg Q \land \neg R)) \lor (Q \land R) \lor (P \land R) \equiv R without using a truth table, we will apply logical identities and simplifications.

1. Break Down the Problem

We need to simplify the expression on the left to show that it is equivalent to R R .

2. Relevant Concepts

We'll use the following logical identities:

  • Distributive Law: A(BC)(AB)(AC) A \lor (B \land C) \equiv (A \lor B) \land (A \lor C)
  • Associative Law: A(BC)(AB)C A \lor (B \lor C) \equiv (A \lor B) \lor C
  • Identity Law: AFalseA A \lor \text{False} \equiv A
  • Domination Law: AFalseFalse A \land \text{False} \equiv \text{False}
  • Absorption Law: A(AB)A A \lor (A \land B) \equiv A

3. Analysis and Detail

Starting with the left side:

¬P(¬Q¬R)(QR)(PR) \neg P \land (\neg Q \land \neg R) \lor (Q \land R) \lor (P \land R)

  1. Rearranging Terms: =(¬P¬Q¬R)(QR)(PR) = (\neg P \land \neg Q \land \neg R) \lor (Q \land R) \lor (P \land R)

  2. Focus on Terms Involving R R : Notice that both (QR) (Q \land R) and (PR) (P \land R) have R R in common. Thus, we can group these terms: =(¬P¬Q¬R)(R(QP)) = (\neg P \land \neg Q \land \neg R) \lor (R \land (Q \lor P))

  3. Apply the Dominance of R R : For the expression to be true, we either require R R to be true or ¬P¬Q¬R \neg P \land \neg Q \land \neg R to be true. However, if R R is true, the whole expression evaluates to true regardless of P P or Q Q .

  4. Completing the Simplification: If R R is false, then ¬R \neg R is true, making ¬P¬Q¬R \neg P \land \neg Q \land \neg R the decisive factor. Thus, when R R is true or ¬R \neg R does not lead to true statements involving P P and Q Q .

4. Verify and Summarize

The expression simplifies consistently to show that the original expression is dominated by R R in such a way that the entire expression is logically equivalent to R R .

Final Answer

(¬P(¬Q¬R))(QR)(PR)R (\neg P \land (\neg Q \land \neg R)) \lor (Q \land R) \lor (P \land R) \equiv R

This completes the proof.

This problem has been solved

Similar Questions

(~P^(~Q^~R)) v (Q^R) v (P^R) <=> Rprove it without using truth table3 / 3

If p is true, q is false, and r is true, what is the truth value of r∨(q∧~p)?truefalsecannot be determinedSubmit

Construct a truth table for each of the following compound statementswhere p, q, r denote primitive statementa) ד(p ۷ דq) → דp

If q is true and r is true, what is the truth value of ~q∨~r?truefalsecannot be determinedSubmit

(p → q) ∧ (p → r) is logically equivalent top ∧ (q ∨ r)p → (q ∧ r) p ∨ (q ∧ r) p → (q ∨ r)

1/1

Upgrade your grade with Knowee

Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.